2020
DOI: 10.1002/jhet.4129
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted synthesis, biological activities, and in silico investigation of some benzimidazole derivatives

Abstract: Some derivatives of 2-substituted benzimidazole were prepared via coupling of N-methyl-o-phenylenediamine or o-phenylenediamine with different aromatic aldehydes catalyzed by Ni(OAc) 2 in the presence of chloroform under microwave-assisted conditions. Structural confirmation of all synthesized molecules was investigated by FT-IR, 13 C NMR, 1 H NMR, ESI-MS, and Elemental analysis. All prepared molecules were examined for in-vitro pharmaceutical activities like antibacterial, antifungal, antimalarial, antituberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A microwave-assisted, Ni(II) catalyzed novel preparation of 2,6-disubstituted and 1,2,6-trisubstituted benzimidazoles were achieved by Patel and his group (Figure 15) [62]. The in-vitro antimicrobial studies of the title compounds (57) against gram-positive and gram-negative bacteria and fungal strains showed an improved activity exhibited by them when compared with ampicillin, a standard drug.…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…A microwave-assisted, Ni(II) catalyzed novel preparation of 2,6-disubstituted and 1,2,6-trisubstituted benzimidazoles were achieved by Patel and his group (Figure 15) [62]. The in-vitro antimicrobial studies of the title compounds (57) against gram-positive and gram-negative bacteria and fungal strains showed an improved activity exhibited by them when compared with ampicillin, a standard drug.…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
“…The antimicrobial and antifungal activities of these benzimidazole derivatives were then evaluated. It was found that some compounds such as ( 61) and (62), were proved to be a better substitute than the standard drugs trimethoprim sulfamethoxazole and miconazole for antimicrobial and antifungal activities, respectively (Figure 16).…”
Section: Antibacterial and Antifungal Activitymentioning
confidence: 99%
“…[63] We present the synthesis, antibacterial, antimalarial, anti-tubercular, and antioxidant evaluation of a novel series of benzimidazole derivatives in response to the foregoing findings and in continuation of our work on benzimidazole derivatives. [31,64] As the number of viable drug molecules in some serious diseases is limited, repurposing of existing drugs or modification of existing drug may be the best way to solve the current scenario. [65] The flexible benzimidazole group is a large target for changing its structure and transforming it into useful compounds for further research into various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] Benzimidazole is a vitamin B12 component that is linked to the purine DNA base and the intoxicating caffeine. [ 31 ] Because of their importance in a variety of industries, including nutrition, cosmetics, and medicines, many scientists have studied their chemistry and have produced a wide range of benzimidazole derivatives over the last few decade. [ 32 ] Benzimidazole derivatives have been found to be effective in numerous biochemical and pharmacological activities [ 33 ] such as anti‐HIV, [ 34 ] antihistaminic, [ 35 ] antioxidant, [ 36 ] antiulcer, [ 37 ] antimalarial, [ 38 ] analgesic, [ 39 ] anti‐tubercular, [ 40 ] antiinflammatory, [ 41 ] antihypertensive, [ 42 ] antimicrobial, [ 43 ] antiprotozoal, [ 44 ] antihelmintic, [ 45 ] anticancer, [ 46 ] antidiabetic, [ 47 ] antihypertensive, [ 48 ] DNA binding, [ 49 ] and antifungal [ 50 ] activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation